2017
DOI: 10.1002/cam4.1259
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of postoperative pneumonia following cancer surgery in adult patients with selected solid cancer: results of “Cancer POP” study

Abstract: The aim of this study was to investigate the incidence and risk factors of postoperative pneumonia (POP) within 1 year after cancer surgery in patients with the five most common cancers (gastric, colorectal, lung, breast cancer, and hepatocellular carcinoma [HCC]) in South Korea. This was a multicenter and retrospective cohort study performed at five nationwide cancer centers. The number of cancer patients in each center was allocated by the proportion of cancer surgery. Adult patients were randomly selected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Because the intervention of preoperative oral care by a dentist was not standardized, the quality of the procedures was dependent on the specific hospital or dentist. No data were obtained on several potential confounders, including BMI, smoking status and functional dependency. The results may not be generalizable to other countries because the study included only Japanese patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the intervention of preoperative oral care by a dentist was not standardized, the quality of the procedures was dependent on the specific hospital or dentist. No data were obtained on several potential confounders, including BMI, smoking status and functional dependency. The results may not be generalizable to other countries because the study included only Japanese patients.…”
Section: Discussionmentioning
confidence: 96%
“…The study analysed approximately 500 000 patients, representing almost all those undergoing major cancer surgery in Japan. It was possible to adjust for numerous factors to eliminate potential confounders, including several previously reported confounding factors (age, sex, hypertension, diabetes mellitus, pulmonary disease, type of surgery and poor general condition).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified numerous patient-related or procedure-related risk factors for POP after femoral neck fracture surgery. In most but not all studies, multiple variables, including older age, male sex, and the presence of several key clinical comorbidities such as chronic obstructive pulmonary disease (COPD), 5 obesity, 7,8 tobacco smoking, 9 prior stroke, 3 impaired preoperative pulmonary function, 10,11 cognitive and functional premorbid status 12 and cardiovascular disease 3 have been identified as risk factors for POP.…”
Section: Introductionmentioning
confidence: 99%
“…Agostini et al [16] have noted that smoking increases postoperative pulmonary complications such as increased hospital mortality, intensive care unit admission rate, and hospital length of stay. Jung et al [32] have also shown that smoking is one of independent risk factors for the development of post-operative pneumonia in cancer patients.…”
Section: Discussionmentioning
confidence: 97%